Variation in bystander cardiopulmonary resuscitation delivery and subsequent survival from out-of-hospital cardiac arrest based on neighborhood-level ethnic characteristics - Blewer, Audrey L. (Circulation, 2019)
BACKGROUND: Bystander cardiopulmonary resuscitation (B-CPR) delivery and survival from out-of-hospital cardiac arrest (OHCA) varies at the neighborhood level, with lower survival seen in predominantly Black neighborhoods. Despite Hispanics being the fastest growing minority population in the US, few studies have assessed whether the proportion of Hispanics in a neighborhood is associated with B-CPR delivery and survival from OHCA. We assessed whether B-CPR rates and survival vary by neighborhood-level ethnicity. We hypothesized that neighborhoods with a higher proportion of Hispanics have lower B-CPR rates and lower survival. METHODS: We conducted a retrospective cohort study, using data from the Resuscitation Outcomes Consortium (ROC) Epistry at US sites. Neighborhoods were classified by census tract, based on percentage of Hispanic residents: < 25%, 25%-50%, 51%-75%, or > 75%. We independently modeled the likelihood of receipt of B-CPR and survival by neighborhood-level ethnicity controlling for site and patient-level confounding characteristics. RESULTS: From 2011-2015, ROC collected 27,481 US arrest events; after excluding pediatric arrests, EMS-witnessed arrests, or arrests occurring in a healthcare or institutional facility, 18,927 were included. B-CPR was administered in 37% of events. Among neighborhoods with <25% Hispanic residents, B-CPR was administered in 39% of events, while it was administered in 27% of events among neighborhoods with >75% Hispanic residents. Compared with <25% Hispanic neighborhoods in a multivariable analysis, OHCA in predominantly Hispanic neighborhoods had lower B-CPR rates (51%-75% Hispanic: OR: 0.79 (CI:0.65-0.95), p=0.014, >75% Hispanic: OR: 0.72 (CI: 0.55-0.96), p=0.025) and lower rates of survival (global p-value: 0.029, >75% Hispanic: OR: 0.56 (CI: 0.34-0.93), p=0.023). CONCLUSIONS: Individuals with OHCA in predominantly Hispanic neighborhoods were less likely to receive B-CPR and had lower likelihood of survival. These findings suggest an important need to understand the underlying disparities in CPR delivery and an unmet CPR training need among Hispanic communities.